Female aggression in flies - Bath, E (2016)
Competition among individuals for access to resources crucial for survival and reproduction is ubiquitous across the animal kingdom. However, most research has focused on male-male competition over access to mates. Female-female competition (hereon "female competition") over resources vital for reproduction, such as food to provision offspring, nesting sites, or social dominance, has been largely neglected. In this thesis, I aim to contribute to the growing body of literature examining female competition by investigating female competition over food in two species of fly. start by assessing the role of an exaggerated secondary sexual trait (eyespan) as a signal in female competition in the stalk-eyed fly Teleopsis dalmanni. Sexual selection theory argues that females only possess exaggerated traits as a result of correlation with males and that they play no functional role. I find that eyespan is an honest indicator of condition but does not appear to function as a signal in either male or female intrasexual encounters, as previously argued. Next, I consider the effects of mating on female aggression in the fruit fly Drosophila melanogaster. I find that mating doubles the amount of time females spend fighting over food. The ability to produce eggs is not required for this effect, but the receipt of sperm is essential. I also find that the magnitude of the effects of mating is determined by a female’s developmental environment – mating significantly increases a female’s chance of winning if she is raised at high larval density, but has no effect on her chances of winning if she is raised at low larval density. Finally, I find suggestions that variation in males and their ejaculates could alter levels of post-mating female aggression, suggesting that post-mating female aggression could potentially be under sexual conflict.